2015
DOI: 10.2460/ajvr.76.8.719
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of immediate- and extended-release formulations of levetiracetam in dogs

Abstract: All ER formulations of levetiracetam had similar pharmacokinetic properties in healthy dogs, with some exceptions. Studies will be needed to evaluate the clinical efficacy of the various formulations; however, findings suggested that twice-daily administration of ER formulations may be efficacious in the treatment of seizures in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
4
12
0
Order By: Relevance
“…The pharmacokinetics of levetiracetam have been extensively evaluated in human patients, dogs, cats, and, more recently, in adult horses [13,14,[22][23][24][25][26]. The results of the current study in foals are similar to those reported in adult horses [14] with minor differences in elimination half-life, volume of distribution and clearance that are likely attributable to agerelated differences in these mechanisms.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The pharmacokinetics of levetiracetam have been extensively evaluated in human patients, dogs, cats, and, more recently, in adult horses [13,14,[22][23][24][25][26]. The results of the current study in foals are similar to those reported in adult horses [14] with minor differences in elimination half-life, volume of distribution and clearance that are likely attributable to agerelated differences in these mechanisms.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have evaluated the difference between IR and ER tablets in multiple veterinary species including adult horses. ER formulations of levetiracetam given to adult dogs as an intact tablet were shown to have significantly lower C max , as well as a longer T max as compared with IR formulations [24]. Plasma half-lives and elimination rate constants were not significantly different between preparations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The LP group had lower peak concentration ( C MAX ) and AUC than did the other 2 treatment groups. The values obtained for C MAX and AUC in the L and LZ groups are comparable to those obtained in a previous study evaluating the disposition of LEV‐XR in healthy dogs after single PO dosing at 30 mg/kg …”
Section: Discussionsupporting
confidence: 85%
“…More recently, an extended‐release formulation of levetiracetam (LEV‐XR) became available, and this drug has gained acceptance as an AED in dogs. The pharmacokinetics of LEV‐XR have been evaluated in 2 single dose studies involving healthy dogs, both of which supported q12h dosing to maintain blood concentrations within the reference range for humans (5‐45 μg/mL) . No studies have evaluated the disposition of LEV‐XR when administered as maintenance treatment to dogs with epilepsy, either with or without other AEDs.…”
Section: Introductionmentioning
confidence: 99%